Laparoscopic Treatment of Morgagni-Larrey Diaphragmatic Hernia with Reposition of the Transverse Colon in Patients with Cardiac Comorbidity. Clinical Observation - Usenko, Oleksandr Yu.; Tyvonchuk, Oleksandr S.; Vynogradov, Roman I.; Zhytnik, Dmytro Yu. (Ukrainian Journal of Cardiovascular Surgery, 2023)
Morgagni-Larrey hernia is a rare form of diaphragmatic hernia (2-5% of cases) usually diagnosed in children; in adults, it is often detected in emergency cases or accidentally, during examinations or during surgery. The symptoms of the disease are non-specific, so the diagnosis is made using imaging methods (computed tomography is the gold standard). Currently, there is no single method of treating Morgagni-Larrey hernias. Closure of the defect is performed with or without the use of various mesh prostheses through the abdominal or thoracic route; open or minimally invasive access. The aim. To conduct a retrospective analysis of the treatment of adult patients with a Morgagni-Larrey diaphragmatic hernia, including those with cardiovascular comorbidity, with a comparison of symptoms, contents of the hernial sac, with the use of laparoscopic techniques and composite mesh prostheses. Materials and methods. The results of the treatment of three patients with a Morgagni-Larrey hernia in the period from 2020 to 2022 at the Shalimov National Institute of Surgery and Transplantation are shown. In two patients, the content of the hernial sac was a loop of the transverse colon, in one, the content of the hernial sac was a greater omentum. Taking into account the accompanying cardiovascular pathology, an interdisciplinary council consisting of a surgeon, anesthesiologist, and cardiologist recommended laparoscopic surgical intervention. Laparoscopic allogeneoplasty with composite prosthesis implantation was performed in three patients. Conclusions. The laparoscopic method of treating diaphragmatic hernias is safe and effective. The use of composite prostheses in combination with tension closure of the defect allows to reduce the risk of recurrence of the disease in the distant postoperative period.